Petrology of Jurassic coal, Hill River area, Perth Basin, Western Australia - Suwarna, Nana (Curtin University, 1993)
The Early Jurassic coal samples for the study were obtained from CRA Exploration Pty Ltd. (CRAE), drilled in the Gairdner and Mintaja Blocks, Gairdner Range of the Hill River Area, northern Perth Basin, Western Australia. The area is located approximately 280 km north of Perth. The coal measures subcrop in a half- graben bounded by the Lesueur-Peron Fault in the west, and the Warradarge Fault in the east. The coal occurs within the shallow sequence of the Cattamarra Member which is also described as the Cattamarra Coal Measures of the Cockleshell Gully Formation. Six sub-seams of seam G, namely G1 to G6, from the six drill cores, were examined for petrological and geochemical investigation. The coal predominantly comprises of banded, dull banded, and dull lithotypes, with minor bright banded, bright and fusainous types. Based on maceral analyses, the dominant maceral groups are vitrinite and inertinite, whilst the exinite and mineral matter are in minor contents. The vitrinite content has a range between 47.2% to 73.0%, and it is composed mainly of telocollinite and desmocollinite. The inertinite is dominated by semifusinite, fusinite, and inertodetrinite, and it has a range from 10.4% to 24.8%. The exinite group varies between 7.2% to 20.8% in content, and it is represented by sporinite, cutinite, alginite and resinite.The mineral matter dominated by clays and pyrite, ranges between 4.5% to 20.6%. The microlithotype analyses shows that the vitrite plus clarite content varies from 47.0% to 70.0%, intermediates between 8.0% to 26.0%, whilst inertite plus durite content is relatively low, varying from 6.55% to 14.0%. The maximum reflectance of vitrinite has a value between 0.47% and 0.53%, which represents rank at sub-bituminous level based on the Australian rank values and corresponding to the sub-bituminous A and B rank of the ASTM classification and to the metalignitous type of the Pareek classification. On the basis of carbon and hydrogen content, the coal is categorised as per-hydrous meta- to ortho-lignitous type. The trace elements As, B, Be, Cd, Co, Cr, Cu, Ga, Mn, Mo, Ni, Pb, Sr, Th, U, V, Y, Zn, and Zr, are spectrographically analysed in the coal ash. The B content in the coal supports the presence of marine influence during peat deposition in the basin. On the basis of lithotype, maceral, microlithotype, trace element distribution, pyrite and total sulphur in the coal, the depositional environment for coal and the coal measures, is interpreted as an upper to lower delta type within a regressive phase of marine transgression.